Increasing Human-Tool Interaction via the Web - Ball, Thomas; Halleux, Jonathan "Peli" de; Leijen, Daan; Swamy, Nikhil (11th ACM SIGPLAN-SIGSOFT Workshop on Program Analysis for Software Tools and Engineering, 2013)
Software tools researchers can accelerate their ability to learn by exposing tools to users via web technologies, allowing them to observe and test the interactions between humans and tools. At Microsoft Research, we have developed a web service (http://www.rise4fun.com/) for such a purpose that is available for community use.